The Effectiveness of Hypnotherapy in Reducing Stress among Individuals with Mental Health Disorders: A Quasi-Experimental Study with a Control Group - Ruswadi, Indra; Wennie, Jummai; Susiani, Ani; Masliha, Masliha (Jurnal Berita Ilmu Keperawatan, 2025)
Individuals with mental health disorders frequently experience elevated levels of stress and anxiety, which negatively impact their overall well-being. Hypnotherapy has been explored as a complementary nursing intervention to reduce psychological distress, yet its effectiveness in psychiatric settings remains under-researched. Objective: This study aimed to evaluate the effectiveness of hypnotherapy in reducing stress and anxiety levels among individuals with mental health disorders. Methods: A quasi-experimental pretest-posttest control group design was employed involving 80 participants diagnosed with psychiatric disorders, randomized into an intervention group (n = 40) and a control group (n = 40). The intervention group received six individual hypnotherapy sessions over four weeks, while the control group received standard psychiatric care. Stress and anxiety levels were measured using the Perceived Stress Scale (PSS-10) and the Beck Anxiety Inventory (BAI). Data were analyzed using paired t-tests and ANCOVA, with effect sizes and 95% confidence intervals calculated. Results: Participants in the hypnotherapy group showed a significant reduction in stress levels (mean difference = -8.4; 95% CI: -10.1 to -6.7; p < 0.001) and anxiety levels (mean difference = -7.4; 95% CI: -9.0 to -5.8; p < 0.001) compared to the control group. The effect sizes were large for both outcomes (Cohen’s d > 0.8). Additionally, 90% of participants in the intervention group reported high satisfaction with the treatment. Conclusions: Hypnotherapy appears to be an effective complementary intervention for reducing stress and anxiety in psychiatric patients. However, given the limited follow-up duration and sample size, future studies should investigate long-term effects, cultural factors, and integration into nursing practice.